Dynamic-Triaxial Tests of Dynamic Shear Modulus and Damping Ratio for sandy silt in Beijing area. Issue 5 (April 2019) - Kang, Xiandong; Wang, Fei
Abstract: To study on relationship between dynamic shear modulus and damping ratio with shear strain, a new dynamic-triaxial test is performed on sandy silt in Beijing area. The testing data of the dynamic-shear modulus are compared with the existing statistical data in Beijing area and the statistical curve to prove the rationality of the test results. Comparsion presents a good agreement.